2022
DOI: 10.3928/24748307-20221013-01
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Health Literacy, Self-Efficacy, and Self-Care Behaviors in Older Adults With Hypertension in the North of Iran

Abstract: Background: Hypertension is the main risk factor for cardiovascular disease. Low level of health literacy is more common in people with hypertension. Evidence suggests that hypertension is preventable and can be controlled by modifying lifestyle and improving self-care behaviors. Objective: This study aimed to determine the relationship between health literacy, self-efficacy, and self-care behaviors in older adults with hypertension. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, after adjustments for covariates, adequate health literacy is associated with the odds of reporting no problems with self-care, mobility, usual activities, and anxiety/depression only. The existing literature supports the link between these specific dimensions of HRQoL and health literacy, based on some demographic groups [ 52 , 53 ] and a few common chronic conditions [ 54 , 55 ]. For example, the significant influence of health literacy on self-care behaviors has been documented in patients with diabetes [ 54 ], hypertension [ 55 ], and heart failure [ 56 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, after adjustments for covariates, adequate health literacy is associated with the odds of reporting no problems with self-care, mobility, usual activities, and anxiety/depression only. The existing literature supports the link between these specific dimensions of HRQoL and health literacy, based on some demographic groups [ 52 , 53 ] and a few common chronic conditions [ 54 , 55 ]. For example, the significant influence of health literacy on self-care behaviors has been documented in patients with diabetes [ 54 ], hypertension [ 55 ], and heart failure [ 56 ].…”
Section: Discussionmentioning
confidence: 96%
“…The existing literature supports the link between these specific dimensions of HRQoL and health literacy, based on some demographic groups [ 52 , 53 ] and a few common chronic conditions [ 54 , 55 ]. For example, the significant influence of health literacy on self-care behaviors has been documented in patients with diabetes [ 54 ], hypertension [ 55 ], and heart failure [ 56 ]. Adequate health literacy is linked to lower disease activity and improved physical functioning among patients with rheumatic diseases [ 57 ].…”
Section: Discussionmentioning
confidence: 96%
“…In this study, higher levels of general self-efficacy were associated with higher levels of health literacy in all statistical models. In other populations, an association between self-efficacy and health literacy has been identified for patients with diabetes 39 , 40 , patients with coronary disease 41 , patients in cardiac rehabilitation 42 , and older adults with hypertension 43 . In stroke survivors, a previous study found a positive association between health literacy and self-efficacy in the use and understanding of medication 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of positive health behaviors also declines with age due to individual limitations [ 4 ] and systemic obstacles posed by poverty, isolation, poor literacy levels, and the absence of elderly-centric healthcare policies. Moreover, compromised health literacy and self-efficacy further impede the translation of healthcare messages into tailored self-care among slum geriatrics [ 5 ].…”
Section: Introductionmentioning
confidence: 99%